18F−Prostate−Specific Membrane Antigen PET/CT imaging for potentially resectable pancreatic cancer (PANSCAN−2): a phase I/II study - Jisce R. Puik; Thomas T. Poels; Gerrit K. J. Hooijer; Matthijs C. F. Cysouw; Joanne Verheij; Johanna W. Wilmink; Elisa Giovannetti; Geert Kazemier; Arantza Farina Sarasqueta; Daniela E. Oprea-Lager; Rutger-Jan Swijnenburg (Cancer Imaging)
Abstract Background Current diagnostic imaging modalities have limited ability to differentiate between malignant and benign pancreaticobiliary disease, and lack accuracy in detecting lymph node metastases. 18F-Prostate-Specific Membrane Antigen (PSMA) PET/CT is an imaging modality used for staging of prostate cancer, but has incidentally also identified PSMA-avid pancreatic lesions, histologically characterized as pancreatic ductal adenocarcinoma (PDAC). This phase I/II study aimed to assess the feasibility of 18F-PSMA PET/CT to detect PDAC. Methods Seventeen patients with clinically resectable PDAC underwent 18F-PSMA PET/CT prior to surgical resection. Images were analyzed both visually and (semi)quantitatively by deriving the maximum standardized uptake value (SUVmax) and tumor-to-background ratio (TBR). TBR was defined as the ratio between SUVmax of the primary tumor divided by SUVmax of the aortic blood pool. Finally, tracer uptake on PET was correlated to tissue expression of PSMA in surgical specimens. Results Out of 17 PSMA PET/CT scans, 13 scans demonstrated positive PSMA tracer uptake, with a mean SUVmax of 5.0 ± 1.3. The suspected primary tumor was detectable (TBR ≥ 2) with a mean TBR of 3.3 ± 1.3. For histologically confirmed PDAC, mean SUVmax and mean TBR were 4.9 ± 1.2 and 3.3 ± 1.5, respectively. Although eight patients had histologically confirmed regional lymph node metastases and two patients had distant metastases, none of these metastases demonstrated 18F-PSMA uptake. There was no correlation between 18F-PSMA PET/CT SUVmax and tissue expression of PSMA in surgical specimens. Conclusions 18F-PSMA PET/CT was able to detect several pancreaticobiliary cancers, including PDAC. However, uptake was generally low, not specific to PDAC and no tracer uptake was observed in lymph node or distant metastases. The added value of PSMA PET in this setting appears to be limited. Trial registration The trial is registered as PANSCAN-2 in the European Clinical Trials Database (EudraCT number: 2020–002185-14). Graphical Abstract